2017
DOI: 10.1002/cncr.30712
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of short‐term dysphagia after transoral robotic surgery for squamous cell carcinoma of the oropharynx

Abstract: BACKGROUND Transoral robotic surgery (TORS) for oropharyngeal squamous cell carcinoma (OPSCC) has been associated with improved long-term dysphagia symptomatology as compared to chemoradiation. Dysphagia in the perioperative period has been inadequately characterized. The objective of this study is to characterize short-term swallowing outcomes after TORS for OPSCC. METHODS Patients undergoing TORS for OPSCC were prospectively enrolled. The Eating Assessment Tool 10 (EAT-10) was used as a measure of swallowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 28 publications
4
49
1
2
Order By: Relevance
“…For example, prior studies have demonstrated how certain interventions (including incentive spirometry, chest physiotherapy, and oral care) can reduce postoperative pulmonary complications . In addition, a recent study demonstrated how the implementation of a standardized speech and language pathology‐driven postoperative swallowing assessment and intervention care pathway essentially eliminated 30‐day dysphagia‐related readmissions in TORS patients …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, prior studies have demonstrated how certain interventions (including incentive spirometry, chest physiotherapy, and oral care) can reduce postoperative pulmonary complications . In addition, a recent study demonstrated how the implementation of a standardized speech and language pathology‐driven postoperative swallowing assessment and intervention care pathway essentially eliminated 30‐day dysphagia‐related readmissions in TORS patients …”
Section: Discussionmentioning
confidence: 99%
“…In addition, dysphagia or dehydration accounted for 8.5% of readmissions, as is also consistent with past studies estimating that dysphagia-related readmissions account for 4.7% to 7.8% of readmissions after TORS. 20 In fact, prior studies have shown that virtually all (98%) patients undergoing TORS will eventually tolerate an oral diet, but the majority (57.4%) will experience dysphagia for the first postoperative month and will at least require compensatory strategies. 20 Dysphagia and dehydration were significant contributors to readmission in our cohort; 18.8% of patients readmitted required gastrostomies and 11.9% of individuals received nutrition via nasogastric tube.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The article by Albergotti et al in this issue of Cancer alludes to the “big picture” ramifications of treatment for HPV oropharyngeal squamous cell carcinoma (OPSCC) on swallowing in its introduction and then focuses on the more modest goal of cataloging and analyzing short‐term sequelae of transoral robotic surgery (TORS) in a prospective manner. The results are not surprising: some OPSCC patients have preoperative swallowing dysfunction; all TORS patients experience postoperative difficulty, which peaks in the immediate postoperative weeks and improves by 30 days; a few patients have longer‐term dysfunction of swallowing; and most patients can cope functionally during this immediate postoperative period without the need for feeding tubes.…”
mentioning
confidence: 99%